Pengaruh Model Problem Based Learning (PBL) Berbantuan Media Canva AI Terhadap Hasil Belajar Kognitif IPA Siswa Sekolah Dasar - Hilma Fauziah; Fitri Nuraeni; Primanita Sholihah Rosmana (JURNAL ASIMILASI PENDIDIKAN, 2026)
The low cognitive learning outcomes of elementary school students remain a challenge in the learning process. Therefore, an alternative solution is needed to address this issue. This study aimed to identify and analyze the effect and differences in the improvement of cognitive learning outcomes between students who were taught using the Problem Based Learning (PBL) model assisted by canva AI media and those who used the Think Pair Share (TPS) cooperative learning model. This study employed a quasi-eksperimental method with a nonequivalent control group design. The research sample consisted of 25 stundents in the experimental class and 25 stundents in the control class. Data were collected through pretest and posttest instruments. The results of the coefficient of determination test showed that the PBL model assisted by canva AI media contributed 64,8% to students’ cognitive learning outcomes. In addition, the N-Gain analysis revealed that the experimental class achieved an improvement of 62% in the moderately effective category, while the control class achieved 45% in the less effective category. These findings indicate that the Problem Based Learning (PBL) model assisted by Canva AI media is more effective as an alternative learning approach for improving elementary school students' cognitive learning outcomes.